Lake- and channel-bottom temperatures in the Mackenzie Delta, Northwest Territories 1 This article is one of a series of papers published in this CJES Special Issue on the theme of Fundamental and applied research on permafrost in Canada. 2 Polar Continental Shelf Project Contribution 03511. - Ensom, T.P.; Burn, C.R.; Kokelj, S.V. (Canadian Journal of Earth Sciences, 2012)
Temperature loggers were placed in 17 lakes and 13 channels throughout the Mackenzie Delta to determine the annual mean bottom temperature ([Formula: see text]) and its spatial and temporal variation for June 2009 – June 2010. The lakes were classified as perched or connected, depending on the duration of their connection to the channel hydrologic system. Average [Formula: see text] values for nine perched lakes, five channels, and eight connected lakes distributed throughout the Mackenzie Delta were 5.5, 4.6, and 3.4 °C, respectively. The range of [Formula: see text] among all instrumented water bodies in the Delta was 4.0 °C. Over the year, bottom temperatures ranged from >20 °C in midsummer to –5 °C in midwinter, with relative stability between freeze-up in mid-October and breakup at the beginning of June. Channel, perched, and connected lake [Formula: see text], and mean annual near-surface ground temperatures of –4 °C in alluvial sedge wetlands and –2.25 °C in forest, were used to estimate that about 60% of Delta lakes and nearly the entire channel network maintain through-taliks.